Analysis of Final Semester Assessment Question Items for Class XI Indonesian History Subjects - Hanifah, Faridatun; Lanoix, Alexandre (Universitas Negeri Semarang, 2024)
This research aims to determine the quality of the final semester assessment (PAS) questions in the Indonesian History subject Class Quantitative analysis is reviewed from the aspects of validity, reliability, level of difficulty, distinguishing power, and effectiveness of distractors. The results of the qualitative analysis of the research showed that the material aspect was met at 96%, the construction aspect at 95.14%, and the language aspect at 73.5%. Judging from the distribution of cognitive domain levels, category (C1) has 7 questions (14%), category (C2) has 35 (70%) questions, category (C3) has 3 questions (6%) and category (C4) has 5 questions (10%). The results of the quantitative analysis of the validity aspect showed that 39 questions (78%) were valid while 11 questions (22%) were invalid. The reliability of the questions is very high at 0.862. From the level of difficulty, 10 (20%) questions were declared difficult, 25 questions (50%) were medium and 15 questions (30%) were easy. Looking at the aspect of differentiating power, there are 6 (12%) questions in the poor category, 7 (14%) questions in the fair category, 26 (52%) questions in the good category, and 9 (18%) questions in the very good category, while the total category is 2 bad. (4%) questions. Judging from the effectiveness of the distractor, the category is very good 21 (42%) questions, functioning well 10 (20%) questions, functioning quite well 10 (20%) questions, functioning poorly 5 (10%) questions, and functioning not well/poorly 4 (8%) questions. Overall, the quality of the questions in terms of quantitative analysis is not good.